Manipulating liquid plugs in microchannel with controllable air vents - Liu, Hao-Bing (2013)
An air venting element on microchannel, which can be controlled externally and automatically, was demonstrated for manipulating liquid plugs in microfluidic systems. The element’s open and closed statuses correspond to the positioning and movement of a liquid plug in the microchannel. Positioning of multiple liquid plugs at an air venting element enabled the merging and mixing of the plugs. Besides these basic functions, other modes of liquid plug manipulations including plug partitioning, multiple plug mixing, and spacing adjustment between liquid plugs, were realized using combination of multiple elements. The structure, operation, and some functions of the element were demonstrated with a microfluidic chip application. The performances of the element including its failure modes, threshold flow rate, and structural optimization were also discussed.